(untitled) (Bangladesh Journal of Medical Science, 2021)
Gender-based violence (GBV) and poor mental health have received particular attention among healthcare professionals, policymakers, and researchers amid the COVID-19 pandemic. This paper presents a review of available literature to understand the dynamics of GBV and its mental health impact in the context of COVID-19. Confinement and control by abusive partners, social and economic disruption, and restricted access to healthcare services were identified as the main contributing factors of GBV. The paper elaborates on the contribution of broader socioeconomic determinants of health as well as cultural and societal factors of victimization in shaping GBV by placing specific populations or individuals in a more vulnerable position within the society based on their gender. Socioeconomic determinants included socioeconomic status, education, migration and racial, ethnic, or gender-based minoritisation. Cultural and societal factors of victimization are mostly related to gender-based structural power discrepancies and communication patterns. Evidence suggests a complex relationship between COVID-19 specific stressors, such as health anxiety and intolerance of uncertainty, GBV, and mental health issues. COVID-19 stressors might directly trigger the mechanism of aggression and cause physical or psychological violence and associated mental health implications in victims, or it might be mediated by pre-existing mental health issues experienced by perpetrators. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.17-25